DAILY AND ANNUAL DAILY TREND ANALYSIS FOR GREATER ZAB RIVER FLOW AT DERALOK STATION - IBRAHIM, SAYRAN A.; MAHMOUD, KHAMLEEN A.; KLARI , ZAHRAA M.; ASWAD, FAWAZ KH. (Journal of Duhok University, 2023)
This study examines the trends in daily and annual discharge data from the Deralok station in northern Iraq over a 16-year period (2004-2019). To analyze these trends, several statistical methods were employed, including the innovative trend approach, the non-parametric Mann-Kendall test (MK), and Sen's slope estimator. Linear regression was also used to establish relationships between variables. The results of the annual discharge analysis reveal a clear increasing trend. The innovative trend method indicated positive slopes, with a value of B = 12.37, which is greater than 0. This positive trend was further supported by the Mann-Kendall test, where both tau values were positive, measuring 0.574 and 4.6, respectively, for Sen's slope estimator. Additionally, the linear regression analysis demonstrated a positive slope, amounting to 4.306 m³/year, indicating a consistent increase in annual discharge. Furthermore, this positive trend was observed across all months, from January to December. These findings collectively suggest a notable upward trend in discharge over the study period, with statistical evidence supporting the observed increases